2016
DOI: 10.1097/scs.0000000000003000
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Versus Microscopic Transsphenoidal Surgery for Pituitary Tumors

Abstract: These data conclude that, compared with MTS, ETS needs longer operation time and results in more intraoperative blood loss, but appears to achieve higher GTR rate for Knosp grade III pituitary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…2%. [22][23][24][25][26][28][29][30][31][32][33][35][36][37][38][39][40][41][42][43]50 The rate of recovery from hormonal deficits in our study is greater than that found by other researchers. Most of our patients (83.9%) showed stable or improved hormonal deficits.…”
Section: Perioperative Outcomescontrasting
confidence: 64%
See 4 more Smart Citations
“…2%. [22][23][24][25][26][28][29][30][31][32][33][35][36][37][38][39][40][41][42][43]50 The rate of recovery from hormonal deficits in our study is greater than that found by other researchers. Most of our patients (83.9%) showed stable or improved hormonal deficits.…”
Section: Perioperative Outcomescontrasting
confidence: 64%
“…Other studies have reported rates of vision improvement from as low as 23% to as high as 100%. [22][23][24][25][26][28][29][30][31][32][33][34][37][38][39][40][41][42][43]50 In our study, no patients had worsened vision after surgery. This is consistent with results found by other researchers who generally saw a very low rate of worsened visual deficits after surgery, on the order of 0%e3.…”
Section: Perioperative Outcomessupporting
confidence: 40%
See 3 more Smart Citations